Minimizing Ambiguity Using Geo-electrical Investigations: Implications for Understanding the Hydro-geologic Setting of a Complex Sub-surface Geology in Oderigha and Environs, Southeastern Nigeria - Peter O, Odong,; David B, Agabi,; Aniedi A, Udo,; Obinna C, Dinneya, (IJRDO-Journal of Applied Science, 2016)
Geo-electric investigations using the schlumberger array was carried out in order to understand the hydrogeologic setting in Oderigha and environs. Soundings were made in 18 different locations in the study area to obtain depth to aquifer units, and thickness of aquifer units. The simulated results from the VES points reveal the presence of 4-5 geo-electric layers. The top layer comprises clay, sand, siltstone intercalations. Layers underneath the top soil are the silty shale, shale, water saturated shaly sandstone and sandstone aquifer. The area is also characterized with high depth to sandstone aquifer which varies from 100m to 240m. The aquifer is overlain by a massive embedded shale conductive layer. At the extreme of North Eastern part of the study area, depths to aquifer are at about 3m to 40m, with VES location 15 having a thickness of about 17m. Aquifer thickness in the study area varies from 17m to 120m. Cross sectional analyses of AA1 , BB1and CC1 in the study area reveals that, VES no. 2, 14, 9, 18 and 11 will be the best locations to drill boreholes for sustainable groundwater development in the area of study to serve the communities. It is also observed that this VES points are located close to the communities. Aquifer resistivity value along the cross sections varies from 689Ωm to 66.94Ωm. The transmissivity varies between 3.5x10-2m2 /s to 4.68x100m2 /s, above the aquifer units in the study area is a widely distributed thick saturated shaly conductive layer. Borehole construction in the area must be preceded by a detailed geophysical survey with current electrode spacing of at least 600m and above.